Trends in social inequality in loneliness among adolescents 1991–2014. (24th July 2018) - Madsen, K R; Holstein, B E; Damsgaard, M T; Rayce, S B; Jespersen, L N; Due, P
Abstract: Background: Loneliness and social inequality in health are important public health concerns. We examined (i) trends in loneliness among adolescents from 1991 to 2014 in Denmark and (ii) trends in social inequality in loneliness. Methods: Study population: 11–15-year olds in random samples of schools in 1991, 1994, 1998, 2006 and 2014, n = 19 096. Loneliness was measured by a single item and social background by parents' occupational social class (OSC). We calculated absolute (%) differences in loneliness between high and low OSC and relative differences by odds ratio for loneliness. Results: Across all surveys, 6.3% reported feeling lonely. The prevalence increased from 4.4% in 1991 to 7.2% in 2014. The prevalence of loneliness in high, middle and low OSC was 5.8, 5.9 and 8.0%. The increase in loneliness was more pronounced in higher than lower OSC, resulting in a decreasing absolute social inequality in loneliness. The statistical interaction between OSC and survey year was significant, P = 0.0176, i.e. the relative social inequality in loneliness also decreased from 1991 to 2014. Conclusion: The prevalence of loneliness increased from 1991 to 2014. The social inequality in loneliness decreased in both absolute and relative terms because of a rising prevalence of loneliness among children from high OSC.